Antivascular endothelial growth factor agents pretreatment before vitrectomy for complicated proliferative diabetic retinopathy: a meta-analysis of randomised controlled trials. Issue 8 (15th December 2017) - Zhao, Xin-yu; Xia, Song; Chen, You-xin
Abstract : Background/aims: To evaluate the efficacy of antivascular endothelial growth factor (anti-VEGF) agents pretreatment before vitrectomy for patients with complicated proliferative diabetic retinopathy (PDR). Methods: The PubMed, Embase and the Cochrane Central Register of Controlled Trials were searched up to June 2017 to identify related studies. The Peferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines were followed. The StataSE V.12.0 software was used to analyse the relevant data. The weighted mean difference, relative risk and their 95% CIs were used to assess the strength of the association. Results: 14 randomised controlled trials involving 613 patients were assessed, the anti-VEGF pretreatment group included 289 patients and the control group included 324 patients. Our analysis indicated that anti-VEGF pretreatment before vitrectomy for complicated PDR could facilitate much easier surgery regarding less intraoperative bleeding, less endodiathermy, shorter duration of surgery, less iatrogenic retinal breaks, less frequency of using silicone oil and relaxing retinotomy (P<0.05). Additionally, anti-VEGF pretreatment could also achieve better postoperative best-corrected visual acuity, less early recurrent vitreous haemorrhage (VH) and quicker absorption of recurrent VH (P<0.05). However, the incidence of late recurrent VH, recurrent retinal detachment or related secondary surgery could not be reduced (P>0.05). Conclusion: The pretreatment of anti-VEGF agents before vitrectomy for patients with complicated PDR might facilitate much easier surgery and better visual rehabilitation, reduce the rate of early recurrent VH and accelerate its absorption. Moreover, future better-designed studies with larger sample sizes are required to further evaluate the efficacy of different anti-VEGF agents and reach a firmer conclusion.